ABUNDANCE AND DISTRIBUTION PATTERNS OF GASTROPODA ON MANGROVE FORESTIN THE AREA OF DESA ANAK SETATAHDISTRICTS RANGSANG BARAT KEPUALAUAN MERANTI REGENCY RIAU PROVINCE - Inka Wahyuni; Aras Mulyadi; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT             This research was conducted in April 2019 with the aim of finding out the abundance and distribution patterns of gastropods in the mangroves of Anak Setatah Village.Determination of the sampling location is done by purposive sampling, which is to determine the sampling point intentionally based on certain objectives.Sampling was carried out in the mangrove area of Anak Setatah Village with different mangrove forest conditions and gastropod identification was carried out at the Marine Biology Laboratory, Faculty of Fisheries and Maritime Affairs, Riau University.The results showed that the total number of species found were 8 gastropod species.In the mangrove mono species 4 gastropod species were found and the mangrove multi species species were found 8 gastropod species, while the highest gastropod abundance was found in the mangrove mono species at observation station IV, which was 23.16 ind/m2 and the lowest was in the multi species mangrove area. at observation station 1 which is 5.36 ind/m2. Key word :Abundance, Distribution Patterns, Anak Setatah Village